User Interface dan Social Media Marketing Sebagai Pendorong Keputusan Pembelian pada E-Commerce Tokopedia - Sarah Dien Hawa (Jurnal Sistem Informasi dan Teknologi Peradaban, 2022)
Tokopedia is one of the e-commerce sites with the most visitors in Indonesia in the 2022 quarter. During this period Tokopedia has an average of 158.3 million website visitors per month, the highest compared to its competitors. Before the pandemic, namely 2019, Tokopedia only had 65.9 million website visitors per month. Then, at the beginning of the 2020 pandemic, Tokopedia visitors dropped slightly, but after that the trend continued to increase. If added up during the period 2019 to 2022 the number of visitors to the Tokopedia website has grown by around 140%. The increase in the number of visitors indicates an increase in consumer purchasing decisions. Using 97 respondents using Tokopedia, this research shows that user interfaces and social media marketing have a positive influence on consumer purchasing decisionsKeyword: user interface, social media marketing, purchase decision, e-commerce